Redeeming laughter : the comic dimension of human experience - Berger, Peter L., 1929-2017 (De Gruyter, 2014)
Amid the variety of human experiences, the comic occupies a distinctive place. It is simultaneously ubiquitous, relative, and fragile. In this book, Peter L. Berger reflects on the nature of the comic and its relationship to other human experiences. Originally published in 1997, the second edition includes a new preface reflecting on Berger's work in the intervening years, particularly on the relationship between humor and modernity.